Antimicrobial and Angiogenic Hybrid Scaffold for Regenerative Endodontics. (2022) - Dubey, N.; Ribeiro, J.S.; Ferreira, J.A.; Xu, J.; Bordini, E.A.; Qu, L.; Mei, L.; Schwendeman, A.; Bottino, M.C.
Abstract : Purpose/Aim: This study sought to engineer a hybrid antimicrobial and angiogenic scaffold comprised of both fiber and hydrogel components that is cytocompatible, biodegradable and provides sustained release of antimicrobial drugs for infection ablation and support angiogenesis. Materials and Methods: Minocycline- (MINO) and clindamycin- (CLIN) modified micro/nanofibers were processed via electrospinning. The fibrous meshes were subsequently grounded via cryomilling and embedded in methacrylated gelatin (GelMA) hydrogel to create injectable hybrid scaffolds. The processed electrospun fibers and cryomilled microparticles were characterized via scanning (SEM) and Fourier transform infrared spectroscopy (FTIR). The effects of microparticles on hydrogel degradability, swelling properties, drug release kinetics and antimicrobial efficacy against oral pathogens were systematically assessed by agar diffusion assay, SEM, and confocal microscopy (CLSM) of the infected dentin specimens. Cytocompatibility was investigated using the tetrazolium reduction (MTS) assay using stem cells from human exfoliated deciduous teeth treated with extracts from hydrogel for up to 21 days. We analyzed the angiogenesis potential of the MINO and CLIN in vitro via capillary-like tube formation assay using human umbilical vein endothelial cells (HUVECs), as well as in vivo using a subcutaneous rat model. Results: The SEM showed bead-free micro/nanofibers with average fiber diameter decreasing with presence of CLIN. The cryomilled electrospun microparticles were distributed in GelMA showing fibrous mesh and hydrated gel structure of the scaffold. The addition of 1% CLIN and 2.5% of MINO showed significant increase in the swelling ratio. All hydrogels were biodegradable, however, GelMA loaded with antibiotic microparticles degraded at different times depending on the antibiotics and their concentration. CLSM and SEM analyses revealed that after exposure to antibiotic-laden hybrid scaffolds, nearly complete elimination of viable bacteria on the dentin surface and inside the dentinal tubules was observed. Importantly, the presence of antibiotics inhibits bacterial growth with increased cell viability compared with GelMA hydrogel only. In culture, CLIN significantly enhanced the formation of capillary-like structures of HUVECs when compared with MINO. In vivo, subcutaneously implanted hybrid scaffold with CLIN stimulated greater vascular growth and recruited more von Willebrand factor than the control and MINO Conclusions: Hybrid scaffolds with sustained release antibiotics for endodontic infection ablation and improved cell viability can be synthesized using the protocol outlined in this study. CLIN-loaded scaffolds demonstrated the ability to support endothelial cells and angiogenesis, which may have positive implications for the overall regenerative outcome.